Software for certification of professional ability CIP- CD Apurímac, Abancay - Achulli Valderrama, Luzmery (2019)
The research is based on the development of Application Software for the Location of Information of the members of the Association of Engineers of Peru - Departmental Council of Apurímac - Abancay. The type of research was quasi experimental design, using methodology the XP , php programming language, mysql, framework mvc laravel for software development. The sample was 75, where the results of the objectives were the following: the information location time was optimized at 71.5%, the quality of attention was improved since 100% of users rated as excellent, 73.3% Of colleagues, they qualify as good and 55.5% improved the reporting time. Concluding that the software The Software significantly contributes to the information location of the colleague in the Association of Engineers of Peru - Apurímac Departmental Council - Abancay.